(untitled) (Revista Torreón Universitario, 2023)
The constant advance of new technologies leads to modifications in the manufacturing industry that seeks to innovate in different tools to continue advancing parallel to the 4.0 revolution. The competition now shows a tendency to modify jobs and filter the selection of candidates to meet the requirements of a company. Terms such as flexibility, optimization, efficiency and value creation are key aspects to consider as essential skills in hiring staff. The objective of this article is to delve into the new skills required from professionals to adapt to the changes that this new stage of the industry brings.